Ritual and Communication in the Graeco-Roman World - Eftychia Stavrianopoulou (dir.) (Presses universitaires de Liège, 2006)
The analysis of the dynamic nature of rituals has become a heuristic tool for the investigation not only of religious behaviour and beliefs, but also for the study of social practice and communication in ancient and modern societies. From public assembly gatherings and funerals to celebration of cult feasts or the honouring of individuals, rituals mark socially important occasions, define beginnings and endings, and aid social transitions. Thus, rituals carry all kinds of messages intended to...